The Nature of Prophetic Genes in Tafsir Perspective: Relation of Primary School Children's Character Education - Slamet Firdaus (IAIN Syekh Nurjati Cirebon, 2022)
AbstractDiscussing education, especially Islamic education, humans are debatable regarding their nature. It is closely related to the prophetic gene that causes humans to be positioned as animals who are good at saying, thinking creatures, and educated creations. The method used in this article uses textual exegesis. Education has urgency as fitrah mukammilah (perfect nature) in developing fitrah majbūlah (instilled nature) by referring to fitrah munazzalah (inherited nature), which is the guide in achieving perfection as a person who has self-pity. Educational and pedagogical efforts that are integrated with the belief in the will of Allah SWT are factors that cannot be ignored. In addition to integrating educators' purity, skills, and intellect with their spiritual actualization.Keywords: Islamic education, prophetic genes, the urgency of education, intellectual piety. AbstrakMembahas mengenai pendidikan, khususnya pendidikan Islam, manusia menjadi ajang perdebatan, termasuk menyangkut fiṭrah-nya yang berhubungan erat dengan gen kenabian yang menyebabkan manusia didudukkan menjadi hewan yang pandai berujar, makhluk berfikir, dan ciptaan berpendidikan. Metode yang digunakan dalam dalam artikel ini menggunakan textual exegesis. Pendidikan mempunyai urgensi sebagai fiṭrah mukammilah (fitrah penyempurna) dalam menumbuhkembangkan fiṭrah majbūlah (fitrah yang ditanamkan) dengan mereferensi kepada fiṭrah munazzalah (fitrah yang diturunkan) yang menjadi petunjuknya untuk mencapai kesempurnaan sebagai insan yang memiliki kesalehan diri. Upaya edukatif dan pedagogis yang terintegrasi dengan keyakinan akan kehendak Allah swt sebagai Maha Penentu merupakan faktor yang tidak bisa diabaikan, di samping unsur integrasi kesalehan ketrampilan dan intelektual para pendidik dengan aktualisasi spiritualnya.Kata kunci: pendidikan islam, gen kenabian, urgensi pendidikan, kesalehan intelektual.